Study on TNFRSF mRNA Alterations and P53 Mutation in Head and Neck Squamous Cell Carcinoma - Thavarajah Rooban; Immanuel Joseph; Selvan Preetha; Joshua Elizabeth; Umadevi Krishna Mohan Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Head and neck squamous cell cancer (HNSCC) is a common cancer worldwide. It has been associated with TP53 mutation and chronic inflammation. The control genes of inflammation, Tumor Necrosis Factor Receptor Superfamily (TNFRSF) in HNSCC has not been widely reported. The impact of the TNFRSF and survival and cell death regulation signalling (SCDRS) can be studied at protein, gene, mRNA and transcription level. In this manuscript, the association of mRNA of TNFRSF and SCDRS genes in treatment naïve HNSCC with TP53 mutation is studied. Materials and Methods: TP53 mutation, tobacco use and mRNA levels of TNFRSF and SCDRS genes of 520 HNSCC cases were collated and analysed. Statistical and differential expression (DE) analysis was performed. Results: A total of 12 genes of the 51 genes studied were DE between TP53 subgroups. They were SCDRS genes (BAD, CASP9, GSK3B, NFKB2, TGFBR1, TGFBR2) and TNFRSF genes (TNFRSF10A/11B/14/25/6B/9). The network analysis and subsequent KEGG pathway analysis identified several key pathways including vital cancer pathways and transcriptional pathways in cancer. The key genes in the network that modulate TNFRSF and SCDRS mRNA expression in wild and mutant TP53 situation are presented. Conclusion: The present work identified certain key TNFRSF and SCDRS mRNAs that could differ based on TP53 status and count with tobacco use. Also this study identified certain pathways where the gene network could potentially alter the HNSCC progression, treatment response and prognosis. This adds to our knowledge of TP53 and inflammation in HNSCC carcinogenesis.